النص التعليمي في الكتاب المدرسي الجزائري،ودوره في ترسيخ قيم الوطنية- كتاب اللغة العربية للسنة الثانية من التعليم المتوسط ـ أنموذجا ـ (Revue El-Wahat pour les Recherches et les Etudes, 2021)
Educational text is one of the impotant pillars of the educational process , and is also very important for it to go ahead , on consederating that the main action that the educational text has , is to make learning achieves  its role , and touches its desires , such as , social , ethical, and educational ones .       So, from this point of view ,I want to focus on one of the important fanction of educational text , which is planting the national spirit and make students and teachers atached to their town and nation , by taking the arabic language book for the second year of average , as a model.            Keywords: Algerian legal textbook, National textbook, Arabic language book, second year intermediate